Analisis Pengelolaan Limbah Kulit Durian di Provinsi Riau Terhadap Potensi Ekonomi dan Dampak Lingkungan - Ariyanti, Dita; Rimantho, Dino; Maryana, Roni; Sekarini, Artanti; Hasibuan, Monalisa; Riza, Subkhan; Utiya Syah, Shinta (IPTEKIN Jurnal Kebijakan Pembangunan dan Inovasi, 2024)
Durian, known as the "King of Fruits" in Southeast Asia, is economically important in Indonesia, particularly in Riau Province. It not only serves as a local delicacy but also has export and agro-tourism potential. However, data from the Riau Central Statistics Agency (BPS) show fluctuating plantation areas and production rates from 2019 to 2022, with a decrease in plantation areas but varying production levels, peaking in 2022. These fluctuations affect durian rind waste generation, posing environmental concerns. Preliminary studies suggest that current waste management practices are inadequate despite the potential for converting durian rinds into useful products like organic fertilizers or biofuels. This study aims to analyze plantation areas, production rates, and durian rind waste generation in Riau while evaluating consumer attitudes and behaviors regarding waste management. It employs both quantitative methods, such as data collection from BPS and field surveys, and primary methods like questionnaires. Analysis includes descriptive statistics and ANOVA tests to assess waste generation differences across sales locations. The findings indicate significant fluctuations in plantation areas and production, with Kampar district leading in both categories. High waste generation rates underscore the need for improved management strategies. Although consumer surveys show awareness of waste issues, practical implementation lags. This research provides insights into optimizing durian production and waste management, aiming to balance economic benefits with environmental sustainability in Riau Province.